Tribological behaviour of OA-capped WO3 nanoparticles as an additive to base oils - Abdullah S.F.; Radiman S.; Azmi M.; Hamid A.; Ibrahim N.B. (2023)
Oleic acid (OA) capped wolfram (VI) oxide, WO3 nanoparticles were chemically synthesized and characterized by means of Fourier Transform-Infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The tribological properties of the capped WO3 nanoparticles as an additive in base oils were investigated using a four-ball machine. Results show that OA-capped WO3 nanoparticles are able to prevent water adsorption and capable of being dispersed stable in organic solvents which is base oils. The as-prepared capped WO3 nanoparticles have an average size of 15 nm. In addition, OA-capped WO3 nanoparticles as an additive in base oils perform good anti-wear (AW) and anti-friction (AF) properties owing to the formation of a boundary film.